Democracy in the Digital Age: Evaluating the Impact of Social Media on Political Awareness and Participatory Citizenship in Punjab with a Case Study of the 2022 Assembly Elections and the Rise of Issue-Based Campaigning on Platforms like YouTube, WhatsApp - Rozy Rani; Dr. Rajdeep Kaur (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This study critically examines the transformative role of social media in shaping political awareness and participatory citizenship in Punjab, with a special focus on the 2022 Punjab Assembly Elections. As digital platforms increasingly replace traditional media as sources of political information, this research investigates how platforms such as YouTube, WhatsApp, and Instagram have redefined the contours of democratic engagement. The study integrates a case study of the 2022 elections, highlighting how political parties—particularly the Aam Aadmi Party (AAP)—leveraged issue-based digital campaigning to engage rural and urban voters, bypassing legacy media and traditional canvassing methods. The research explores how memes, short videos, influencer endorsements, and mobile-first campaigns contributed to voter mobilization and the articulation of regional political demands. Drawing on secondary data from institutional reports, media analyses, and digital policy frameworks, the paper also considers how social media has empowered youth and marginalized communities by decentralizing political discourse. While celebrating the participatory potential of digital tools, the study also interrogates challenges such as misinformation, surveillance, data privacy breaches, and algorithmic polarization. Ultimately, this research underscores the dual nature of social media as both a democratizing force and a site of contested political narratives, providing nuanced insights into how digital technologies are reshaping political consciousness in Punjab’s evolving electoral landscape.